Structural realism and metatheoretical structuralism - Jaramillo Uribe, Juan Manuel (Estudios de Filosofía, 2014)
Structural realism, in response to criticism known as “pessimistic meta-induction”, argues for the persistence of the mathematical structure of the theories (not the content) in some cases (the limits) when there exist changes in their evolution, so that the success of subsequent theories is explained by the structural retention of previous theories. Although there is no monolithic point of view regarding the realism/anti-realism debate in meta-theoretical structuralism, in this paper we analyze and discuss, from this modelistic proposal, the validity of the central arguments of structural realism as an alternative to standard scientific realism. We follow the distinction of structural realism made by Ladyman between epistemic and ontic structural realism, and although in this paper we will provide a general description of the first, the analysis will focus primarily on the analysis and criticism in the second. To this end, we will use the tools provided by meta-structuralist theory in philosophy of science and, specifically, the identification made therein of theories as classes or sets of models and/or set-theoretic structures. Our purpose here is to clarify, from this meta-theoretical proposal, the basic assumptions of what Sneed called “minimal scientific realism” and its variant, epistemological structural realism, specifically as regards his notion of the proposed structural continuity and the suggestions made by some authors to an appeal to Ramsey’s judgment as justification of structural realism without reference.